2017
DOI: 10.21037/cdt.2017.09.07
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of cardiomyopathies

Abstract: Cardiac computed tomography (CT) is increasingly used in the evaluation of cardiomyopathies, particularly in patients who are not able to undergo other non-invasive imaging tests such as magnetic resonance imaging (MRI) due to the presence of MRI-incompatible pacemakers/defibrillators or other contraindications or due to extensive artifacts from indwelling metallic devices. Advances in scanner technology enable acquisition of CT images with high spatial resolution, good temporal resolution, wide field of view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…CTAs are frequently prospectively gated to reduce radiation dose, but they can also be performed with retrospective gating if there is a desire for the assessment of the LV function or to assess the valvular functional status, 5 this is, however, accompanied by increase in radiation dose as compared to the prospective ECG gating technique.…”
Section: Discussionmentioning
confidence: 99%
“…CTAs are frequently prospectively gated to reduce radiation dose, but they can also be performed with retrospective gating if there is a desire for the assessment of the LV function or to assess the valvular functional status, 5 this is, however, accompanied by increase in radiation dose as compared to the prospective ECG gating technique.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic myocardial strain is a time-consuming technique, a significant expertise is needed, and it is likely to be useful just in determining prognosis [45]. Other echocardiographic limitations include inadequate soft tissue characterization and suboptimal field-of-view in the setting of poor acoustic windows, such as in overweight/obese patients or in those suffering from SARS [52].…”
Section: Role Of Imagingmentioning
confidence: 99%
“…Recently, Lee et al21) demonstrated that mean ECV values for patients with HCM (32.31% ± 0.97%) were significantly higher (p < 0.01) than in healthy subjects (26.32% ± 0.90%) on dual-energy equilibrium or delayed phase cardiac CT. Cardiac CT allows for the evaluation of HCM based on key morphological characteristics (presence, location, distribution, and severity of LVH), LV systolic function, the mitral valve and its apparatus, intraventricular obstruction, extent of myocardial fibrosis with delayed enhancement and ECV measurement (tissue characterization), and the presence of LV crypts. These indicators are used alongside anatomical imaging of the coronary arteries (stenosis, myocardial bridging), particularly when echocardiographic images are suboptimal and CMR is contraindicated 4)49)50)…”
Section: Cardiomyopathy and Myocarditismentioning
confidence: 99%
“…Cardiac CT demonstrates global or regional hypokinesia, focal wall thickening (acute), focal thinning and ventricular aneurysm (chronic), diverse delayed enhancement pattern (transmural, subepicardial, or midmyocardial), and increase in myocardial ECV in cardiac sarcoidosis as well as the involvement of other organs (Figure 10). 21)50)54)…”
Section: Cardiomyopathy and Myocarditismentioning
confidence: 99%
See 1 more Smart Citation